2014
DOI: 10.1073/pnas.1220971111
|View full text |Cite
|
Sign up to set email alerts
|

Effective 2D model does not account for geometry sensing by self-organized proteins patterns

Abstract: By means of a computational model analysis accompanying intriguing experiments, Schweizer et al. (1) claim to show that MinE membrane binding is responsible for selforganized geometry sensing.We investigated the simulation files provided by the authors and found that the model neither accounts for actual MinE membrane interactions nor for any observed MinDE protein patterns. A detailed discussion of our analysis can be found in the supplementary document hosted at http:// arxiv.org/abs/1403.5934. It does not r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
4
13
1
Order By: Relevance
“…This demonstrates that direct MinE membrane interaction is dispensable for pattern formation per se , consistent with mathematical models that do not require the incorporation of direct MinE membrane interaction [35, 39]. …”
Section: Resultssupporting
confidence: 76%
“…This demonstrates that direct MinE membrane interaction is dispensable for pattern formation per se , consistent with mathematical models that do not require the incorporation of direct MinE membrane interaction [35, 39]. …”
Section: Resultssupporting
confidence: 76%
“…The role of MinE membrane binding in determining the system dynamics has become a major focus of in vivo and in vitro study (17,19,20,22,33,34) and computational modeling (24), as well as a matter of considerable debate (35,36). To further examine the role of lingering MinE in patterning, we studied a MinE mutant lacking its MTS, MinE .…”
Section: Solution Concentration Of Min Proteins Oscillates In the Burmentioning
confidence: 99%
“…In fact, essentially only the mechanism introduced in [44] has been analysed in geometries corresponding to Min proteins on flat membranes. Given the harsh criticism this model received [62], it is all the more surprising that to our knowledge no other mechanism is capable of reproducing the travelling Min-protein waves that were observed in vitro. In particular, the model by Huang et al [32], which is used in many current studies, can to our knowledge not reproduce any of the patterns observed in the open geometry.…”
Section: (A) Open Geometriesmentioning
confidence: 99%